Milan, 1967-’68: a young internist meets with Industrial Toxicology - Alessio, Lorenzo (La Medicina del Lavoro, 2019)
It was while working in the emergency department of the general hospital (Ospedale Maggiore) of Milan University, that the writer, then a young internist, realized the importance of the Laboratory of Industrial Toxicology of Clinica del Lavoro (Lab) for the diagnosis of a large number of diseases caused by toxic agents, such as aniline, toluene, “commercial ” trichloroethylene, lead. The analytical methods of the time were not very sensitive and specific, but these tests were useful since the concentrations of the toxic agents in the biological fluids were generally very high. During the 1970’s and 1980’s the performance of the Lab evolved due to a progressive improvement of the analytical quality. Therefore, the capacity in evaluating the toxic agents (metals, solvents, pesticides etc) in the biological fluids in concentrations decidedly lower than those observed in patients with clinical intoxication allowed the use of these tests for the biological monitoring both of workers occupationally exposed and of groups of general population living in highly polluted areas. The identification of the levels of the biological indicators which could be considered “safe” facilitated the use of these tests. On this topic the studies of the Lab contributed to the activities of national and international Agencies, such as SIMLII, ICOH, ACGIH, WHO and above all CEE. From the early 1990’s the activity of the Lab moved progressively from the evaluation of macrodoses to microdoses, this data confirming the efficacy of preventive measures adopted in the previous decades.